2018
DOI: 10.15562/jdmfs.v3i1.731
|View full text |Cite
|
Sign up to set email alerts
|

The speech ability on maxillary denture wearer: a systematic review

Abstract: Objective: Getting information about on influence of denture bases design on speech ability on maxillary denture wearer.Methode: Electronic search in PubMed and Wiley online library databases to find articles that were published in last 20 years; between January 1998 to December 2017 with keywords “denture bases” and “speech”. The articles were then selected by reviewing the title and abstract.Result: The initial search obtained 52 articles. Then selected by involving the inclusion criteria. Finally, it gain 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is important to remember that satisfaction to denture affects patient's quality of life. [8][9][10] Previous studies have shown that many factors can play important role in patient's satisfaction to denture, including denture fabrication technique, patient's factor, and dentist's factor. Among these factors, there are five factors which show more effect to patient's satisfaction, including therapy selection, patient's personality and psychology, patient's oral hygiene, patient's perception about dentist and dental treatment, and communication.…”
Section: Patient's Satisfaction and Expectation To Denturementioning
confidence: 99%
“…It is important to remember that satisfaction to denture affects patient's quality of life. [8][9][10] Previous studies have shown that many factors can play important role in patient's satisfaction to denture, including denture fabrication technique, patient's factor, and dentist's factor. Among these factors, there are five factors which show more effect to patient's satisfaction, including therapy selection, patient's personality and psychology, patient's oral hygiene, patient's perception about dentist and dental treatment, and communication.…”
Section: Patient's Satisfaction and Expectation To Denturementioning
confidence: 99%